(untitled) (Canadian Perspectives on Academic Integrity, 2023)
The aim of this session is to provide insight into the practical application of the principles of equity, diversity, and inclusion (EDI) to the promotion of academic integrity and management of academic misconduct through a practitioner’s lens. This perspective will present the experiences of practitioners working in both the K-12 and post-secondary environments, in which diverse student populations necessitate the implementation of elements of EDI into everyday interactions with learners. The discussion will include awareness of marginalizing factors, provision of voice, and intersectionality relevant to the lived experiences of students. Participants will come away with a renewed understanding of practical ways to apply an EDI lens to promoting academic integrity and managing academic misconduct.